Map positioning support system prototype website / Mohd Azmi Mat Junoh - Mat Junoh, Mohd Azmi (2005)
With the rapid growth of Information Technology, the usage of the Internet and the World Wide Web is nothing new. Internet has become the best, the fastest and the cheapest way of communication nowadays. It has become another prominent way of distributing information other than mass media, television, radio and post. There is no doubt that through these means, information can easily be obtained and utilized, it also means that by using Internet technologies, people can easily get connected, share information and expose to the outside world. Thus the purpose of this project is to develop a prototype for Map Positioning Support System website which has many new features such as interactive map. the website will to provide interactive map where users can search any building within scope and gain the shortest route that have been identified in project scope which provided by website. This project also provide information on news and events happen in UiTM Shah Alam main campus as a prototype for current news and events provide by real Map Positioning Support System Technology. And last one is provide website with easy navigation to allow users to gain information easier and faster. Prototyping methodology has been used to develop and completed this project. As a result, project has achieved all it objectives within scope.